PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP DIVIDEND POLICY DENGAN CORPORATE LIFE CYCLE SEBAGAI VARIABEL MODERASI - Aditia Pramana; Agung Juliarto (Diponegoro Journal of Accounting, 2025)
This study aims to examine the effect of Corporate Social Responsibility (CSR) on dividend policy with the corporate life cycle as a moderating variable. Dividend policy is one of the most complex challenges in corporate finance and represents a crucial decision. CSR funding is considered to provide financial benefits, as it can strengthen relationships with stakeholders, particularly customers. As a result, company performance may improve, ultimately allowing for dividend payments. The corporate life cycle is regarded as a factor influencing CSR and dividend policy, as managerial preferences are shaped by the company’s financial condition. This sample used in this research is financial companies listed in the Indonesia Stock Exchange in the 2016-2024 period. The total final sample used in this research was 102 firm-year observations. Sample selection was carried out using a purposive sanpling method with predetermined conditions and criteria. The analytical method used in this research are Moderated Regression Analysis. The results show that Corporate Social Responsibility does not have a significant effect on dividend policy. This may be due to CSR funding being long term oriented and requiring considerable time to generate benefits, whereas dividend payments are short-term oriented. However, when companies are in the mature stage of the corporate life cycle, CSR begins to affect dividend policy. At this stage, firms tend to have stable financial conditions and generate high profits, enabling them to reinvest through CSR funding while simultaneously distributing dividends